2011
DOI: 10.1111/j.1755-3768.2011.02141.x
|View full text |Cite
|
Sign up to set email alerts
|

The ocular pulse amplitude at different intraocular pressure: a prospective study

Abstract: . Purpose:  To investigate changes in ocular pulse amplitude (OPA) during a short‐term increase in intraocular pressure (IOP) and to assess possible influences of biometrical properties of the eye, including central corneal thickness (CCT) and axial length. Methods:  In a prospective, single centre study, OPA and IOP as measured by dynamic contour tonometry (DCT) were taken before baseline‐ and post‐OPA (delta) intravitreal injection of 0.05 ml anti‐vascular endothelial growth factor agents. Analysis was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
(89 reference statements)
1
7
0
1
Order By: Relevance
“…mmHg) berichten. Der direkte Zusammenhang zwischen der OPA und dem Augeninnendruck konnte auch bei augengesunden Probanden durch eine medikamentöse Drucksenkung[7] oder Steigerung unmittelbar nach intravitrealen Injektionen[8] gezeigt werden. Keine der anderen untersuchten Parameter (Alter, Hornhautdicke, Vorderkammertiefe, Hornhautradius, Astigmatismus, systolischer oder diastolischer Blutdruck, Blutdruckamplitude oder Puls) zeigten einen signifikanten Einfluss auf die OPA.…”
unclassified
“…mmHg) berichten. Der direkte Zusammenhang zwischen der OPA und dem Augeninnendruck konnte auch bei augengesunden Probanden durch eine medikamentöse Drucksenkung[7] oder Steigerung unmittelbar nach intravitrealen Injektionen[8] gezeigt werden. Keine der anderen untersuchten Parameter (Alter, Hornhautdicke, Vorderkammertiefe, Hornhautradius, Astigmatismus, systolischer oder diastolischer Blutdruck, Blutdruckamplitude oder Puls) zeigten einen signifikanten Einfluss auf die OPA.…”
unclassified
“…This phenomenon has been observed in both population-based measurements 1 (0.12 mm Hg of OPA / 1 mm Hg of IOP) and in experiments where saline was injected into the eye to artificially increase IOP (0.05-0.073 mm Hg of OPA / 1 mm Hg of IOP). 9,66 We also observed a decreased pulse volume for a higher baseline IOP, which could be due to a decreased ocular perfusion pressure. This has also been reported in experimen-tal measurements (29% pulse volume decrease as IOP increased from 20 to 40 mm Hg).…”
Section: Our Models Predicted Shearing Of Neural Tissues In the Neuromentioning
confidence: 61%
“…Ocular pulse amplitude (OPA) was not influenced by IOP change following SLT in this group of glaucoma patients. Previous studies have shown that there is a positive correlation between IOP and OPA in healthy subjects (Kaufmann et al 2006;Knecht et al 2011). This is necessary to maintain a relatively constant level of blood flow when IOP changes and is a sign of functioning autoregulation.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that there is a positive correlation between IOP and OPA in healthy subjects (Kaufmann et al 2006;Knecht et al 2011). Previous studies have shown that there is a positive correlation between IOP and OPA in healthy subjects (Kaufmann et al 2006;Knecht et al 2011).…”
Section: Discussionmentioning
confidence: 96%